(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
In this article, the strategy of improving the quality of education in general secondary education institutions on the basis of cluster approach, the principles of pedagogical education, the content of education and the specifics of the field in the organization of joint activities of educational organizations based on a cluster approach, innovative management of the pedagogical process of an educational organization based on a cluster approach, the use of competitive advantages of the territory, pedagogical education On the basis of a cluster approach, it is about ensuring competitiveness in the market of educational services.